2019
DOI: 10.1128/jb.00561-18
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Hybrid Histidine Protein Kinase SinK Acts as a Signal Integrator To Fine-Tune Multicellular Behavior in Myxococcus xanthus

Abstract: His-Asp phosphorelay (also known as two-component signal transduction) proteins are the predominant mechanism used in most bacteria to control behavior in response to changing environmental conditions. In addition to systems consisting of a simple two-component system utilizing an isolated histidine kinase/response regulator pair, some bacteria are enriched in histidine kinases that serve as signal integration proteins; these kinases are usually characterized by noncanonical domain architecture, and the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Movies of M. xanthus development have demonstrated that prior to the onset of sporulation, aggregates are surprisingly dynamic (26, 28). Initial aggregates often dissolve or coalesce, and even mature aggregates can be mobile prior to transition to stationary spore-filled fruiting bodies (26).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Movies of M. xanthus development have demonstrated that prior to the onset of sporulation, aggregates are surprisingly dynamic (26, 28). Initial aggregates often dissolve or coalesce, and even mature aggregates can be mobile prior to transition to stationary spore-filled fruiting bodies (26).…”
Section: Resultsmentioning
confidence: 99%
“…Movies of M. xanthus development have demonstrated that prior to the onset of sporulation, aggregates are surprisingly dynamic (26, 28). Initial aggregates often dissolve or coalesce, and even mature aggregates can be mobile prior to transition to stationary spore-filled fruiting bodies (26). To examine how MrpC NAR affected these transient behaviors, the wild type, P WT - mrpC , and P MUT - mrpC strains were induced to develop under submerged culture conditions, imaged every 30 min from 0 – 72 h in an automated plate reader, and the images assembled into movies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations